Pengaruh Model Game Based Learning Terhadap Pemahaman Konsep Siswa Materi Sistem Pernapasan Manusia Pada Siswa Kelas V - Dini Agustin; Regina Lichteria Panjaitan; Aah Ahmad Syahid (Mataram University, 2026)
The background of this research is the low level of conceptual understanding among fifth-grade students, which is attributed to the limited use of learning models that facilitate active student engagement in the learning process. This study aimed to examine the effect of the Game Based Learning model on fifth-grade students’ conceptual understanding of the human respiratory system. The research employed a quasi-experimental method using a nonequivalent control group design. The participants consisted of fifth-grade elementary school students, with 30 students in the experimental class and 30 students in the control class. Data were collected through observation and testing. The results indicated that the Game-Based Learning model was effective in improving students’ conceptual understanding of the human respiratory system, as evidenced by the higher mean score of the experimental class compared to that of the control class. Therefore, it can be concluded that the Game Based Learning model is more effective than conventional learning methods and can serve as an alternative approach to enhancing fifth-grade students’ conceptual understanding. Furthermore, this study demonstrates that Game-Based Learning helps students improve their understanding of the human respiratory system through direct interaction and active participation in learning activities.